The influence of electromagnetic radiation on extraction process of inulin from roots of dandelion (Taraxacum officinale Wigg.) - Дем’янова, Я. В.; Яблонська, К. М. (Problems of Environmental Biotechnology, 2015)
The influence of microwave electromagnetic radiation (60 GHz) on the efficiency of inulin extraction from the roots of dandelion (Taraxacum officinale Wigg.) was investigated. The greatest effect of the electromagnetic radiation was observed for extract exposure during 25 minutes.